Re;hai enterprise / Anna Jasmine Hariulnizam ...[et al.] - Hariulnizam, Anna Jasmine; Mat Nawi, Muhammad Aiman; Ariuddin, Nadzirah Huda; Mohamad Saifol, Nur Aliesya; Suwandi, Siti Rafhanah (2023)
This business, which name is Re;Hai Enterprise, specialises in selling hijabs produced from premium materials. The items are made of premium cotton, matte satin, chiffon silk, printed jersey, and knit jersey. Every product has well-known characteristics and advantages. For instance, matte satin is wrinkle-resistant and has a distinctive matte appearance. Our business shop is located at Lot 212, Level 2, AEON Tebrau Shopping Center, No. 33A, Jln Harmonium, Taman Desa Tebrau, 81100 Johor Bahru, Johor. This location was chosen specifically because AEON Tebrau Shopping Center is one of the well-known shopping centres in Johor and draws a sizable number of visitors each day. The business will launch in April 6, 2023, and its target market will be primarily female university students and working housewives aged 20 to 40 who live in the area. The sales forecast of the first year is estimated to be RM630,420. Muhammad Aiman, the general manager, is responsible for planning and overseeing the overall operation of the Re;Hai business, which is owned under a partnership agreement. The financial manager, Siti Rafhanah, is in charge of managing the business' investment operations, creating plans for its long-term financial goals, and generating financial reports. The administrative manager, Nadzirah Huda, is in charge of scheduling duties, handling the payroll and personnel databases, and creating reports that other clerical jobs can use. Additionally, standards and procedures were established for this role to make sure that staff employees had appropriate training. The marketing manager, Nur Aliesya, is responsible for developing marketing strategies and stimulating demand for products and services. Anna Jasmine's job as an operational manager is managing the procedures involved in producing a business' goods and/or services. An operations manager, for instance, would be in charge of planning and strategizing as well as all tasks related to ordinary store floor operations.